Diseño de un manual de buenas prácticas de manufactura (bpm) para la microempresa “Servipan” en el sector de Huachi Chico, canton Ambato. - Chicaiza Cando, Mónica Jacqueline (2019)
The right practices of manufacture are elements that can be applicated to all processed food handling and they are a fundamental instrument to produce safe and healthy food for consumers. This research work aims to make a handbook of right manufacture practices (BPM) for “servipan” micro-enterprise, located in Huachi Chico, Ambato city. In order to cariy, out this research, the researchers applied some researche techniques, such as the observation, interviews and survey. These were applied on 16 employees at the company, divided into 6 bakermen, 3 bakers, 5 sellers and 2 administrative people. As a result, all production processes done in the micro-enterprise are carried out in an empirical and traditional way, which represents some production difficulties. All in all, the micro-enterprise needs a handbook of right manufacture practices which will help to improve the production of bakeryand pastry food. As a conclusion, there are different areas where the contamination prevails as much as in the containers to prepare food as staff uniforms who prepares them, 88% of workers consider necessary a rapid implementation of a guide of control processes to make quality goods for the consumer. For these reason, making a handbook of good manufacture practices (BPM) was necessary to improve productive processes. For these reason, to make a handbook of right manufacture practices (BPM) was necessary to improve productive processes.